Climate change mitigation and nature conservation both require higher protected area targets. (16th March 2020) - Roberts, Callum M.; O'Leary, Bethan C.; Hawkins, Julie P.
Abstract : Nations of the world have, to date, pursued nature protection and climate change mitigation and adaptation policies separately. Both efforts have failed to achieve the scale of action needed to halt biodiversity loss or mitigate climate change. We argue that success can be achieved by aligning targets for biodiversity protection with the habitat protection and restoration necessary to bring down greenhouse gas concentrations and promote natural and societal adaptation to climate change. Success, however, will need much higher targets for environmental protection than the present 10% of sea and 17% of land. A new target of 30% of the sea given high levels of protection from exploitation and harm by 2030 is under consideration and similar targets are being discussed for terrestrial habitats. We make the case here that these higher targets, if achieved, would make the transition to a warmer world slower and less damaging for nature and people. This article is part of the theme issue 'Climate change and ecosystems: threats, opportunities and solutions'.